2015
DOI: 10.1002/kin.20910
|View full text |Cite
|
Sign up to set email alerts
|

Oxovanadium(IV)-Salen Ion Catalyzed H2 O2 Oxidation of Tertiary Amines to N -Oxides- Critical Role of Acetate Ion as External Axial Ligand

Abstract: The oxovanadium(IV)-salen ion catalyzed H 2 O 2 oxidation of N,N-dimethylaniline forms N-oxide as the product of the reaction. The reaction follows Michaelis-Menten kinetics and the rate of the reaction is accelerated by electron donating groups present in the substrate as well as in the salen ligand. This peculiar substituent effect is accounted for in terms of rate determining bond formation between peroxo bond of the oxidant and the N-atom of the substrate in the transition state. Trichloroacetic acid (TCA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…This observation demonstrates the formation of a new vanadium species in the reaction mixture. Appearance of such a broad peak near 570 nm region by the addition of oxidant to the reaction mixture containing oxosalen complex has been already noticed in the oxidation of sulfides, [ 68 ] sulfoxides, [ 22 ] phenol, [ 10 ] tertiary amines, [ 21 ] and PMAA. [ 37,39 ] In all these cases, formation of new peak has been interpreted by the formation of adduct between salen complex and H 2 O 2.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This observation demonstrates the formation of a new vanadium species in the reaction mixture. Appearance of such a broad peak near 570 nm region by the addition of oxidant to the reaction mixture containing oxosalen complex has been already noticed in the oxidation of sulfides, [ 68 ] sulfoxides, [ 22 ] phenol, [ 10 ] tertiary amines, [ 21 ] and PMAA. [ 37,39 ] In all these cases, formation of new peak has been interpreted by the formation of adduct between salen complex and H 2 O 2.…”
Section: Resultsmentioning
confidence: 90%
“…The advantages of working with VO(salen) are its high stability and simple method of synthesis from commercially available VOSO 4. [20] Oxovanadium(IV)-salen complexes are widely used as catalyst in the oxidation of tertiary amines, [21] phenols, [10] phenylsulfinylacetic acids, [22] benzoin, [23] alcohol, [24] and oxidative coupling of 2-naphthols. [25] Besides catalytic activity, vanadium acts as an insulinenhancing agent either in the form of its inorganic salts or complexes with organic ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The details of synthesis of salen ligands and oxovanadium(IV)-salen complexes and spectral characterization are given our previous reports [59,61] but the spectral data are collected in the supporting information (Tables S1 and S2). The structure of the oxovanadium(IV)-salen complexes synthesized for the present study are shown in Chart 1.…”
Section: Resultsmentioning
confidence: 99%
“…The ligands [56,57] and oxovanadium(IV)-complexes [58][59][60][61][62][63][64][65] were synthesized by known procedures and characterized by UV-vis, MS, FTIR spectral studies and cyclic voltammetry measurements (Tables S1 and S2). Bovine serum albumin (BSA) and ovalbumin (OVA) were purchased from Ocimum Bioscience and Sigma-Aldrich respectively and used without any further purification.…”
Section: Methodsmentioning
confidence: 99%
“…Also, in homogeneous catalysis, vanadium Schiff base complexes formed with chelating ligands involving hetero atoms are found to be used in a variety of systems [14]. Homogeneous catalysts of oxovanadium(IV) complexes induce organic reactions in the oxidation of sulfides and sulfones [24,25], the epoxidation of alkenes [26,27], the hydroxylation of hydrocarbons [28], the oxidation of alcohols to aldehydes and ketones [29,30], phenols [31] and tertiary amines to N-oxides [32].…”
Section: Introductionmentioning
confidence: 99%